On the Topographical Chronology of Early Mediaeval Cemeteries with Pagan Burial Characteristics in Northern Dalmatia (Archaeologia Adriatica, 2014)
Based on an analysis of the ground-plan of early mediaeval cemeteriesat Maklinovo Brdo in Kašić and at Ždrijac in Nin, the author identifies grave groups dating back further than the last third of the 8th century. The absence of characteristic artefacts upon which a reliable chronology could be determined is explained by economic and social changes in the eastern Adriatic hinterland of the time.
Keywords: Kašić – Maklinovo Brdo; Nin – Ždrijac; cemetery; Early Middle Ages; Late Antiquity; social organisation; economy